Association between medical insurance and life satisfaction among middle-aged and older adults in China: the mediating role of depression - Jian Sun; Peter C. Coyte; Yujiang Liu; Qianqiang Wang (Cost Effectiveness and Resource Allocation)
Abstract Background While studies have reported a positive association between medical insurance and life satisfaction, there is a lack of studies assessing the underlying impact mechanism. The present study aims to investigate the association between Urban and Rural Resident Basic Medical Insurance (URRBMI) and life satisfaction in China, focusing on the mediating role of depression. Methods Using 2018 wave of China Health and Retirement Longitudinal Study, we employed ordered logit regression models to examine the correlation between URRBMI and life satisfaction. Causal mediation analysis was used to analyze the mediating effect of depression on this association. Results URRBMI participation was related to greater life satisfaction (p < 0.01). Depression mediated the correlation between URRBMI and life satisfaction, and the percentage of total effect mediated was 18.20%. Discussion Middle-aged and older adults covered by URRBMI were more likely to have greater life satisfaction than their counterparts because insurance relieved depression. Conclusion Our study highlighted many policy suggestions, such as improving its coverage, establishing a unified information platform, and mobilizing social forces to provide better life services.